A Systematic Review of the Empirical Support for Check-In Check-Out. (April 2016) - Wolfe, Katie; Pyle, Daniel; Charlton, Cade T.; Sabey, Christian V.; Lund, Emily M.; Ross, Scott W.
Tier 2 interventions play an important role within the Positive Behavioral Interventions and Supports framework, bridging the gap between schoolwide Tier 1 interventions and individualized Tier 3 supports. Check-in Check-out (CICO) is a promising Tier 2 intervention for addressing mild problem behavior and potentially preventing the need for more intensive supports. In this systematic review, we synthesize the characteristics, methodological quality, and outcomes of 15 single-subject studies and one group design study examining CICO. The results suggest that CICO can be considered an evidence-based practice for students with problem behavior maintained by adult attention. Versions of CICO that were modified to address other functions (e.g., obtain peer attention, escape from tasks) demonstrated strong effects, but there were not a sufficient number of studies for modified CICO to qualify as an evidence-based practice. We discuss the implications of this review for practitioners as well as future research on CICO.